Android–Based “EDUGARLIN” Application in Increasing Knowledge and Attitudes of Postpartum Mother about Postpartum Fitness - Junengsih, Junengsih; Jehanara, Jehanara; Fitriana, Shentya; Siregar, Mukhlidah Hanum (jitek, 2023)
Knowledge of postpartum fitness includes recognising the danger signs of childbirth, fulfilling nutrition, the physical adaptation of postpartum and breastfeeding mothers, the process of achieving the role of motherhood, adaptation to becoming parents, health promotion for healthy living behaviour, prevention of diseases and complications of puerperium, family planning and the success of exclusive breastfeeding are critical things that postpartum mothers should know. Information technology from smartphones using Android-based applications can be used to increase mothers' knowledge about postpartum fitness. This study aims to analyse the differences in knowledge and attitudes of postpartum mothers to improve postpartum fitness before and after being given the "Edugarlin" application. The research design used a quasi-experimental method with a pre-posttest and control group design. The subjects of this study were postpartum mothers who came to visit the Depok Jaya Inpatient Clinic and PMB IIS Suliystiowati Ciracas East Jakarta for postpartum visits from August to November 2022. Sampling used a purposive sampling technique with a sample counting formula, obtaining as many as 96 respondents, 48 in the treatment group (given the Edugarlin application) and 48 in the control group (paper-based). Data analysis using Wilcoxon Sign Rank Test and Maan Whitney U Test. The study found that knowledge and attitudes about postpartum fitness increased after being given the "Edugarlin" application with a significance value of <0.05. Postpartum fitness knowledge must be continuously improved using various media, one of which is the Edugarlin application.